2004
DOI: 10.1136/bjo.2003.037044
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma patients with high risk ocular pathological features: who needs adjuvant therapy?

Abstract: Aims: To describe the outcome of patients with non-metastatic unilateral retinoblastoma with high risk histopathological features after primary enucleation, and to clarify the need and results of adjuvant therapy. Patients and methods: From 1980 to 2001 adjuvant therapy was recommended only to patients with scleral involvement, post-laminar optic nerve involvement (PLONI) with either a positive margin or associated choroidal involvement, or (before 1994) isolated PLONI. Results: 108 of 224 patients had at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 16 publications
4
103
1
3
Order By: Relevance
“…When we investigated the possible relationship between tumor focality at diagnosis and the asynchronous bilateralization of retinoblastoma, we detected multifocal lesions in 1 (33.3%) of the 3 patients with asynchronous bilateralization of retinoblastoma (P > resection margin; P < 0.05] and poor tumor differentiation with no detectable rosettes or fleurettes [4 (80%) of 5 patients with poor tumor differentiation; P < 0.05], findings that are in agreement with those of several studies [5,11,12,15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When we investigated the possible relationship between tumor focality at diagnosis and the asynchronous bilateralization of retinoblastoma, we detected multifocal lesions in 1 (33.3%) of the 3 patients with asynchronous bilateralization of retinoblastoma (P > resection margin; P < 0.05] and poor tumor differentiation with no detectable rosettes or fleurettes [4 (80%) of 5 patients with poor tumor differentiation; P < 0.05], findings that are in agreement with those of several studies [5,11,12,15].…”
Section: Discussionsupporting
confidence: 89%
“…It seems that optic nerve invasion and poor tumor differentiation are more closely correlated with metastatic disease than to the metachronous bilateralization of the disease [10][11][12]. Furthermore, a statistically significant correlation was found between negative NSE staining and asynchronous bilateralization of retinoblastoma (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of choroidal invasion varies greatly in various reported series, ranging from 15.2% to 62%. 2,23,[25][26][27] We observed choroidal invasion in 47.4% of cases, with 24.6% of cases having massive involvement. Comparisons of optic nerve and choroidal invasion in other major series are given in Tables 3 and 4, respectively.…”
Section: Commentmentioning
confidence: 96%
“…The significance of isolated anterior segment involvement remains debatable, but we have previously witnessed metastasis in such cases, so this was included as a factor. 10 Some authors 5,13 have suggested that anterior segment involvement and isolated choroidal invasion are not risk factors for metastasis. The other major source of variation is related to the definition of massive choroidal invasion.…”
Section: Discussionmentioning
confidence: 99%